Difference between revisions of "009C Sample Midterm 3, Problem 2"

From Math Wiki
Jump to navigation Jump to search
m
 
(3 intermediate revisions by the same user not shown)
Line 1: Line 1:
<span class="exam">For each the following series find the sum, if it converges. If
+
<span class="exam">For each the following series find the sum, if it converges.  
you think it diverges, explain why.
 
  
::<span class="exam">(a) (6 points) &nbsp;&nbsp;&nbsp;&nbsp; <math style="vertical-align: -50%">\frac{1}{2}-\frac{1}{2\cdot3}+\frac{1}{2\cdot3^{2}}-\frac{1}{2\cdot3^{3}}+\frac{1}{2\cdot3^{4}}-\frac{1}{2\cdot3^{5}}+\cdots .</math>  
+
<span class="exam">If you think it diverges, explain why.
 +
 
 +
<span class="exam">(a) &nbsp;<math style="vertical-align: -50%">\frac{1}{2}-\frac{1}{2\cdot3}+\frac{1}{2\cdot3^{2}}-\frac{1}{2\cdot3^{3}}+\frac{1}{2\cdot3^{4}}-\frac{1}{2\cdot3^{5}}+\cdots </math>  
 
<br>
 
<br>
  
::<span class="exam">(b) (6 points) &nbsp;&nbsp;&nbsp;&nbsp; <math style="vertical-align: -75%"> \sum_{n=1}^{\infty}\,\frac{3}{(2n-1)(2n+1)}.</math>
+
<span class="exam">(b) &nbsp;<math style="vertical-align: -75%"> \sum_{n=1}^{\infty}\,\frac{3}{(2n-1)(2n+1)}</math>
 +
<hr>
 +
[[009C Sample Midterm 3, Problem 2 Solution|'''<u>Solution</u>''']]
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
! Foundations: &nbsp;
 
|-
 
|One of the important series to know is the '''Geometric series.''' These are series with a common ratio <math style="vertical-align: 0%">r</math> between adjacent terms which are usually written
 
|-
 
|
 
::<math>\sum_{k=0}^{\infty}a_{0}r^{k}.</math>
 
|-
 
|These are convergent if <math style="vertical-align: -22%">|r|<1</math>, and divergent if <math style="vertical-align: -22%">|r|\geq1</math>. If it is convergent, we can find the sum by the formula
 
|-
 
|
 
::<math>S=\frac{a_{0}}{1-r},</math><br>
 
|-
 
|where <math style="vertical-align: -12%">a_{0}</math> is the first term in the series (if the index starts at <math style="vertical-align: 0%">k=2</math> or <math style="vertical-align: 0%">k=6</math>, then "<math style="vertical-align: -12%">a_{0}</math>" is actually the first term <math style="vertical-align: -12%">a_{2}</math> or <math style="vertical-align: -12%">a_{6}</math>, respectively).
 
|-
 
|Another common type of series to evaluate is a '''telescoping series''', where the telescoping better describes the partial sums, denoted <math style="vertical-align: -15%">S_k</math>.  Most of the time, they are presented as a fraction which requires '''partial fraction decomposition'''.
 
|-
 
|This can be accomplished fairly quickly via a shortcut when the factors in the denominator are linear and share the same coefficient on <math style="vertical-align: 0%">n</math>.
 
|-
 
|'''Example.''' Suppose we wish to decompose the fraction <math style="vertical-align: -22%">\frac{4}{(n-2)(n+1)}</math>.  First, consider the difference
 
|-
 
|
 
::<math>\frac{1}{n-2}-\frac{1}{n-1}</math>
 
|-
 
|If we combine this to a common denominator, we find
 
|-
 
|
 
::<math>\frac{1}{n-2}\cdot\frac{n+1}{n+1}-\frac{1}{n+1}\cdot\frac{n-2}{n-2}\,=\,\frac{n+1-(n-2)}{(n-2)(n+1)}\ =\ \frac{3}{(n-2)(n+1)}.</math>
 
|-
 
|To have a 1 in the numerator, we would just multiply by <math style="vertical-align: -25%">1/3,</math> or the reciprocal of the difference between the two constants. Thus
 
|-
 
|
 
::<math>\begin{array}{rcl}
 
{\displaystyle \frac{4}{(n-2)(n+1)}} & = & {\displaystyle 4\cdot\frac{1}{(n-2)(n+1)}}\\
 
\\
 
& = & 4\cdot{\displaystyle \frac{1}{3}\left(\frac{1}{n-2}-\frac{1}{n+1}\right).}
 
\end{array}</math>
 
|-
 
|Notice the pattern: for any fraction of the form<math>\frac{1}{(x+a)(x+b)}</math> where<math>a<b,</math> we have
 
|-
 
|
 
::<math>{\displaystyle \frac{1}{(x+a)(x+b)}\,=\,\frac{1}{b-a}\left(\frac{1}{x+a}-\frac{1}{x+b}\right).}</math>
 
|-
 
|In this manner, we can quickly find that
 
|-
 
|
 
::<math>{\displaystyle \frac{1}{n^{2}-25}\,=\,\frac{1}{(n-5)(n+5)}\,=\,\frac{1}{5-(-5)}\left(\frac{1}{n-5}-\frac{1}{n+5}\right)\,=\,\frac{1}{10}\left(\frac{1}{n-5}-\frac{1}{n+5}\right)}</math>
 
|-
 
|As per the so-called telescoping, consider the series defined by
 
|-
 
|
 
::<math>\sum_{n=2}^{\infty}\frac{1}{n^{2}-1}.</math>
 
|-
 
|Using the technique above, we can rewrite the series as
 
|-
 
|
 
::<math>\sum_{n=2}^{\infty}\frac{1}{(n-1)(n+1)}\,=\,\sum_{n=1}^{\infty}\frac{1}{2}\left(\frac{1}{n-1}-\frac{1}{n+1}\right).</math>
 
|-
 
|This means that
 
|-
 
|
 
::<math>\begin{array}{cclcl}
 
S_{2} & = & \frac{1}{2}\left(\frac{1}{1}-\frac{1}{3}\right)\\
 
\\
 
S_{3} & = & \frac{1}{2}\left(\frac{1}{1}-\frac{1}{3}+\frac{1}{2}-\frac{1}{4}\right) & = & \frac{1}{2}\left(\frac{1}{1}+\frac{1}{2}-\frac{1}{3}-\frac{1}{4}\right)\\
 
\\
 
S_{4} & = & \frac{1}{2}\left(\frac{1}{1}-\frac{1}{3}+\frac{1}{2}-\frac{1}{4}+\frac{1}{3}-\frac{1}{5}\right) & = & \frac{1}{2}\left(\frac{1}{1}+\frac{1}{2}-\frac{1}{4}-\frac{1}{5}\right)\\
 
\\
 
S_{5} & = & \frac{1}{2}\left(\frac{1}{1}-\frac{1}{3}+\frac{1}{2}-\frac{1}{4}+\frac{1}{3}-\frac{1}{5}+\frac{1}{4}-\frac{1}{6}\right) & = & \frac{1}{2}\left(\frac{1}{1}+\frac{1}{2}-\frac{1}{5}-\frac{1}{6}\right)\\
 
\\
 
\vdots & \vdots & \vdots\\
 
S_{k} & = & \frac{1}{2}\left(\frac{1}{1}+\frac{1}{2}-\frac{1}{k}-\frac{1}{k+1}\right).
 
\end{array}</math>
 
|-
 
|Notice the pattern; each time there are ''<u>exactly</u>'' two surviving positive terms, and two surviving negative terms. This is ''<u>exactly</u>'' the difference between the two factors <math style="vertical-align: 0%">n-1</math> and <math style="vertical-align: 0%">n+1</math>in the denominator. If we then take the limit, we find
 
|-
 
|
 
::<math>\sum_{n=2}^{\infty}\frac{1}{n^{2}-1}\,=\,\lim_{n\rightarrow\infty}S_{n}\,=\,\lim_{n\rightarrow\infty}\frac{1}{2}\left(\frac{1}{1}+\frac{1}{2}-\frac{1}{n}-\frac{1}{n+1}\right)\,=\,\frac{3}{4}.</math>
 
|}
 
  
&nbsp;'''Solution:'''
+
[[009C Sample Midterm 3, Problem 2 Detailed Solution|'''<u>Detailed Solution</u>''']]
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!(a): &nbsp;
 
|-
 
|This is the easier portion of the problem.  Each term grows by a ratio of <math style="vertical-align: -22%">1/3</math>, and it reverses sign.  Thus, there is a common ratio <math style="vertical-align: -22%">r=-1/3</math>.  Also, the first term is <math style="vertical-align: -22%">1/2</math>, so we can write the series as a geometric series:
 
|-
 
|
 
::<math style="vertical-align: -75%"> \sum_{n=0}^{\infty}\,\frac{1}{2}\left(-\frac{1}{3}\right)^n.</math>
 
|-
 
|Then, the series converges to the sum
 
|-
 
|
 
::<math>S\,=\,\frac{a_{0}}{1-r}\,=\,\frac {1/2}{1-(-1/3)}\,=\,\frac{1/2}{4/3}\,=\,\frac{3}{2}.</math>
 
|}
 
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!(b): &nbsp;
 
|-
 
|
 
|}
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;
 
|-
 
|
 
|}
 
 
[[009C_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']]
 
[[009C_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 08:43, 28 November 2017

For each the following series find the sum, if it converges.

If you think it diverges, explain why.

(a)  

(b)  


Solution


Detailed Solution


Return to Sample Exam